2016
DOI: 10.1175/jamc-d-15-0107.1
|View full text |Cite
|
Sign up to set email alerts
|

Categorizing the Meteorological Origins of Critical Ramp Events in Collective Photovoltaic Array Output

Abstract: Photovoltaic (PV) solar power use is increasing globally. The Australian Capital Territory (ACT) has legislated a renewable energy target of 90% by 2020; to reach this target, use of distributed PV solar arrays is expected to increase. Cloud cover can cause the power output of PV installations to rapidly increase or decrease, resulting in ACT-wide collective ramp events. Accurate forecasts of when the ramp events will occur are needed for electricity providers to plan for these abrupt output changes and to ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Proposed estimation will be useful for power TSO and DSO (electric power companies have a role of TSO and DSO in Japan).The proposed PV power generation estimation method should be useful in the analysis of PV power generation during rapid variations of PV power generation (ie, ramp events) in order to estimate their impact on the power grid, because it provides data with a high temporal and spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed estimation will be useful for power TSO and DSO (electric power companies have a role of TSO and DSO in Japan).The proposed PV power generation estimation method should be useful in the analysis of PV power generation during rapid variations of PV power generation (ie, ramp events) in order to estimate their impact on the power grid, because it provides data with a high temporal and spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed estimation will be useful for power TSO and DSO (electric power companies have a role of TSO and DSO in Japan).The proposed PV power generation estimation method should be useful in the analysis of PV power generation during rapid variations of PV power generation (ie, ramp events) in order to estimate their impact on the power grid, [28][29][30] because it provides data with a high temporal and spatial resolution. Furthermore, the method described in this study may have higher potential for various energy management scenarios in the field of safe energy control (eg, electric power management, energy storage management, electrical transmission, and measures for PV curtailment.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulus clouds (i.e., thunderstorms) often tend to develop rapidly and cause swift decrease of GHI values (i.e., ramp events, see Section 5). Wellby and Engerer, [13]) identified weather types (thunderstorm, cold front, cloud band etc.) for city-scale negative ramp events in Australia.…”
Section: A Case Study Of Cumulus Cloud Simulationmentioning
confidence: 99%
“…Ramp events frequently cause rapid increases and/or decreases of PV power generation. Wellby and Engerer [13] categorize city-scale (defined as a region size of approximately 30 km) ramp events according to meso-scale and synoptic-scale meteorological phenomena (e.g., cold fronts, thunderstorms, cloud bands). If the NWP can accurately predict these meteorological phenomena, then the ramp events can also be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the high‐frequency components of solar irradiance fluctuations and how they generate ramps of PV power, Lave et al analysed clearness index data with 1 second of resolution in 6 locations near each other in San Diego, California . The authors performed a wavelet decomposition to analyse the fluctuations and found a good level of agreement between their results and the model developed by Hoff et al In addition, Wellby and Engerer categorised cloud phenomena and weather phenomena associated with ramps of PV power in the Australian Capital Territory . They showed that the most positive ramps were caused by cloud bands and fog dissipation and that negative ramps can be related with the passage of cold fronts in the area studied.…”
Section: Introductionmentioning
confidence: 99%